Evaluating HPV‐negative CIN2+ in the ATHENA trial. Issue 12 (2nd March 2016) - Petry, Karl Ulrich; Cox, J. Thomas; Johnson, Kristin; Quint, Wim; Ridder, Ruediger; Sideri, Mario; Wright, Thomas C.; Behrens, Catherine M.
Abstract : A post hoc analysis of the ATHENA study was performed to determine whether true HPV‐negative cervical lesions occur and whether they have clinical relevance. The ATHENA database was searched for all CIN2 or worse (CIN2+) cases with cobas HPV‐negative results and comparison was made with Linear Array (LA) and Amplicor to detect true false‐negative HPV results. Immunostaining with p16 was performed on these cases to identify false‐positive histology results. H&E slides were re‐reviewed by the study pathologists with knowledge of patient age, HPV test results and p16 immunostaining. Those with positive p16 immunostaining and/or a positive histopathology review underwent whole tissue section HPV PCR by the SPF10/LiPA/RHA system. Among 46, 887 eligible women, 497 cases of CIN2+ were detected, 55 of which tested negative by the cobas ® HPV Test (32 CIN2, 23 CIN3/ACIS). By LA and/or Amplicor, 32 CIN2+ (20 CIN2, 12 CIN3/ACIS) were HPV positive and categorized as false‐negatives by cobas HPV; nine of 12 false‐negative CIN3/ACIS cases were p16+. There were 23 cases (12 CIN2, 11 CIN3/ACIS) negative by all HPV tests; seven of 11 CIN3/ACIS cases were p16+. H&E slides were available for six cases for re‐review and all were confirmed as CIN3/ACIS. Tissue PCR was performed on the six confirmed CIN3/ACIS cases (and one without confirmation): four were positive for HPV types not considered oncogenic, two were positive for oncogenic genotypes and one was indeterminate. In summary, subanalysis of a large cervical cancer screening study did not identify any true CIN3/ACIS not attributable to HPV. Abstract : What's new? Human papillomavirus (HPV) testing has a high negative predictive value for detecting histological cervical intraepithelial neoplasia (CIN). False‐negative HPV results can occur, however, though their clinical relevance is little understood. Using data from the U.S.‐based ATHENA study, the authors of the present report show that only a very small percentage of CIN grade 3/adenocarcinoma in situ (ACIS) lesions were missed by the cobas HPV Test, which identifies 14 high‐risk HPV types. False‐negatives by cobas testing were compared with Linear Array and Amplicor testing. Most missed CIN3/ACIS cases were associated with HPV types not included in current tests.